Clinical profile of diabetic ketoacidosis in tertiary hospitals in China: a multicentre, clinic‐based study. Issue 2 (2nd July 2015) - Xu, Y.; Bai, J.; Wang, G.; Zhong, S.; Su, X.; Huang, Z.; Chen, G.; Zhang, J.; Hou, X.; Yu, X.; Lu, B.; Wang, Y.; et al.
Abstract: Aims: To evaluate the clinical profile of patients with diabetic ketoacidosis in tertiary hospitals in China. Methods: A retrospective study of patients hospitalized with diabetic ketoacidosis between 2010 and 2012 was carried out in 15 tertiary hospitals around China. Clinical and laboratory data were collected. Patients were classified based on clinical diagnosis and treatment history. Groups were compared for differences in vital statistics and biochemical profiles at presentation. Results: The study comprised 643 patients with diabetic ketoacidosis: 308 patients (47.9%) with Type 1 diabetes, 294 patients (45.7%) with Type 2 diabetes and 41 patients (6.4%) with atypical diabetes. Three hundred and eighty‐eight diabetic ketoacidosis episodes (60.3%) were in patients with known diabetes. The most common precipitating factor was infection (40.1%), followed by unknown causes (36.9%) and non‐compliance with anti‐diabetes treatment (16.8%). At presentation, gastrointestinal symptoms and dehydration were more common in the Type 1 diabetes group. For new‐onset diabetes, only 74.4% and 55.9% of patients were evaluated for β–cell function and autoantibodies for classification. Only 67% of patients with diabetic ketoacidosis received appropriate fluid therapy and 56% patients with severe acidosis received bicarbonate therapy. The length of hospital stay was 10.0 (7.0–14.0) days. The mortality rate was 1.7%, and was much higher in Type 2 diabetes than that in Type 1 diabetes (3.2% vs. 0.4%, P  < 0.01). Conclusions: Type 2 and Type 1 diabetes contribute to a similar proportion of cases presenting with diabetic ketoacidosis in China. Admissions with diabetic ketoacidosis are still associated with significant mortality and prolonged hospitalization. The efficiency of diabetic ketoacidosis management needs to be improved by implementing the updated guidelines.